Effects of intensive vs. standard blood pressure control on cognitive function: Post-hoc analysis of the STEP randomized controlled trial - Fan, Jiali; Bai, Jingjing; Liu, Wei; Cai, Jun (Frontiers in Neurology, 2023)
Background The STEP (Strategy of Blood Pressure Intervention in the older Hypertensive Patients) trial showed that intensive systolic blood pressure (SBP) control resulted in a lower incidence of cardiovascular events than standard treatment. This study analyzed the effects of intensive SBP lowering on cognitive function. Methods STEP was a multicenter, randomized controlled trial of hypertensive patients aged 60–80 years. Participants were randomly assigned (1:1) to SBP goals of 110–130 mmHg (intensive treatment) or 130–150 mmHg (standard treatment). Each individual was asked to complete a cognitive function test (Mini-Mental State Examination; MMSE) at baseline and during follow-up. The primary outcome for this study was the annual change in MMSE score. Subjects with a score less than education-specific cutoff point were categorized as cognitive decline. Results The analysis enrolled 6,501 participants (3,270 participants in the intensive-treatment and 3,231 participants in the standard-treatment groups). Median follow-up was 3.34 years. There was a minor change in MMSE score, with an annual change of −0.001 [95% confidence interval [CI] −0.020, 0.018] and 0.030 (95% CI 0.011, 0.049) in the intensive- and standard-treatment groups, respectively (p = 0.052). Cognitive decline occurred in 46/3,270 patients (1.4%) in the intensive-treatment group and 42/3,231 (1.3%) in the standard-treatment group (hazard ratio 0.005, 95% CI 0.654, 1.543, p = 0.983). Conclusions Compared with standard treatment, intensive SBP treatment did not result in a significant change in cognitive function test score. The impact of intensive blood pressure lowering was not evident using this global cognitive function test. Trial registration ClinicalTrials.gov. Unique identifier: NCT03015311.